Evolução morfológica e funcional do fígado na coexistência de Esquistossomose Mansoni e desnutrição - Couto, Janira Lúcia Assumpção (2006)
In endemic areas of the schistosomiasis mansoni commonly exist association between that parasitosis and malnutrition. It was accomplished an experimental study here through the reproduction of infection and malnutrition, just as happen in the human species. The mice, in number of 75, were divided in four groups, in agreement with the diets (normal or low-protein) and the infection: well-fed ( controls), well-fed with infection, undernourished and undernourished with infection. The experiment had duration of 90 days. Several aspects, concerning to the liver under effects of the two diseases, were examined: occurrence of hepatomegaly, serology indexes of the hepatic function, cytochrome P450 activity and histopathological alterations. The intestinal absorption of proteins was also verified. The hepatomegaly of the infection suffered influence of the nutritional state, because in well-fed animals the absolute weight of the liver was highe(p<0,0001). Biochemical indexes of the hepatic function showed alterations. ALT and AST were more elevated in the well-fed animals with infection, compared to the control(p<0,0001). That can result of the inflammatory process of higher intensity observed in them. All the groups presented elevation of Alkaline Phosphatase, with difference between well-fed and undernourished, both without infection (p<0,001) and likeness among infected groups (p>0,05). The increase of AST and Alkaline Phosphatase in wellfed infected animals allows supposing the cholestasis existence. Levels of Albumin were not different among the groups (p>0,05), though the undernourished ones, infected or not infected, showed them lower. Animals well-fed infected presented higher increase of the Serologic Proteins. They differed from the undernourished ones, with or without infection (p<0,01), that with the smallest results, because the influence of the low-protein diet. Low levels of Glucose were also found in the groups, when compared to the control (p<0,001). Therefore, infection or malnutrition cause hypoglycemia, especially when both it is put upon. The intestinal absorption of proteins was similar between the group control and the others (p>0,05), what demonstrates the preservation of the absorptive function of the mucous membrane in the malnutrition and/or infection, under conditions in this study. The study of the cytochrome P450 revealed that the reduction of the microsomal protein hepatic was due to the infection more than to the malnutrition, the control group was just similar to undernourished (p>0,17) and differed of the groups with infection, well-fed and undernourished (p<0,02). The infection also caused inhibition of the isoenzymes of cytochrome P450, verified by the absence of progesterone hydroxilation by the same ones. In the histological examination was evident that only malnutrition didn't cause alterations in the examined organs. The nutritional state influenced the schistosomiasis evolution, when in the well-fed animals, the granulomatosis inflammation was exacerbated with hyperplastic reactions that caused severe forms observed. It was established the transition period of the acute phase for the chronic phase of the disease